Does Inclusive Leadership Reduce Emotional Dissonance Among Teachers? #x2013; Investigating the Mediating Role of Psychological Empowerment Climate and Organizational Justice (Global Journal of Management and Business Research, 2020)
The role of teachers is of utmost significance in the education system. The emotions of teachers play a vital role in determining their development and wellbeing. Emotional dissonance leads to several negative consequences for both the teachers and the institution and will affect their commitment and overall well-being. Several factors affect the emotions of teachers in the institution. This emotional exhaustion of the teachers can be reduced if the organization has inclusive leaders, provides them a climate of empowerment and follows justice.
Keywords: teachers; inclusive leadership; psychological empowerment climate; organizational justice; emotional dissonance; mediating effect